Analisis dan Simulasi Rangkaian Konverter Buck untuk Efisiensi Tinggi dalam Pengisian Perangkat Portabel 5 Volt - Nizar, Fahrun; Wiryajati, I Ketut; Nababan, Sabar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Technological developments and advances have caused many electrical and electronic devices to almost all use DC voltage sources whose voltage can be adjusted. So a tool is needed to reduce the DC voltage to an adjusted voltage, namely a buck converter. A buck converter is a device that can reduce DC voltage to a lower voltage. This research aims to design an open and close loop buck converter circuit, determine the level of efficiency and the effect of the duty cycle on the output voltage and the error difference value. Investigation and use of MATLAB/SIMULINK software. In this research, the buck converter duty cycle was changed from 5% - 99% in the open loop and the input voltage was 12 volts - 24 volts in the closed loop which worked at a frequency of 50kHz. The output voltage value that approaches 5 volts is a duty cycle of 40% with the voltage obtained being V measured 5.067 volts, V calculated 4.8 volts with an error difference of 0.267 in the open loop circuit and in the closed loop the average difference in output voltage error is obtained from The setting point voltage is 5 volts, namely 1.102.